2012
DOI: 10.1002/cctc.201100242
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenation of Propane over MoOx and POx Supported on Carbon Nanotube Catalysts

Abstract: Catalytic performance of MoOx–POx supported on oxidized carbon nanotube (oCNT) catalysts for oxidative dehydrogenation of propane has been investigated. The catalysts were characterized by XRD, TEM, and IR spectroscopy techniques and then tested through the propane oxidation dehydrogenation reaction. The results reveal that the addition of MoOx significantly improves the catalytic activity but reduces the selectivity to propene. In contrast, adding POx decreases the reactivity and increases the selectivity by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Their high costs when used as bulks bring them to the field of nanoparticle (NP) science, generally applied as metallic NP on top of a substrate or support [ 15 , 16 , 17 , 18 , 19 ]. Since these metals are dispersed as metallic NPs on a support, their chemical activity increases using a considerable small amount of metal.…”
Section: Introductionmentioning
confidence: 99%
“…Their high costs when used as bulks bring them to the field of nanoparticle (NP) science, generally applied as metallic NP on top of a substrate or support [ 15 , 16 , 17 , 18 , 19 ]. Since these metals are dispersed as metallic NPs on a support, their chemical activity increases using a considerable small amount of metal.…”
Section: Introductionmentioning
confidence: 99%
“…Mo is earth abundant and has a similar electronic structure to Cr. Oxides, carbides, and nitrides of molybdenum have thus been widely utilized in catalytic applications, which but are not limited to alkene isomerization, hydrogenation, hydrogenolysis, and hydrodesulfurization. In contrast, as a candidate for catalytic dehydrogenation, Mo-based catalyst has been mainly studied in oxidative dehydrogenation of ethane, propane, and n -butane in previous studies. , For example, the catalytic performances of molybdenum oxides, including MoO 3 crystallites, MoO x monomers, or polymers, are typically affected by the supporting species, the molybdenum oxidation state, and the dispersion of the metals. Wang and co-workers showed that the Mo/MgAl 2 O 4 catalyst can achieve ca.…”
Section: Introductionmentioning
confidence: 99%
“…Corma and Katz have shown that the catalytic perfοrmance of delaminated zeolites is different from that of the same zeolite prior to delamination. Doped MoS 2 , which is used as a catalyst in the oil industry, also seems to be a two-dimensional system whose activity is mainly at the border of the platelets. It has been shown that submonolayers of molybdenum oxide supported on another oxide are better catalysts for methanol oxidation or oxidative dehydrogenation of propane , than MoO 3 powder. The catalytic activity deteriorates when more than a monolayer of molybdenum oxide is added to the support.…”
Section: Introductionmentioning
confidence: 99%
“…Doped MoS2, which is used as a catalyst in the oil industry, also seems to be a two-dimensional system whose activity is mainly at the border of the platelets. [17][18][19] It has been shown that submonolayers of molybdenum oxide supported on another oxide are better catalysts for methanol oxidation [20][21][22][23][24][25][26][27][28][29][30] or oxidative dehydrogenation of propane 23,[31][32][33][34][35] than MoO3 powder.…”
mentioning
confidence: 99%